2006
DOI: 10.2514/1.17854
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Shock Mitigation and Drag Reduction by Pulsed Energy Lines

Abstract: A series of numerical experiments were performed in which energy was deposited ahead of a cone traveling at supersonic/hypersonic speeds. The angle of attack was zero, and the cone half-angles ranged from 15 to 45 deg. The Mach numbers simulated were 2, 4, 6, and 8. The energy was deposited instantaneously along a finite length of the cone axis, ahead of the cone's bow shock, causing a cylindrical shock wave to push air outward from the line of deposition. The shock wave would sweep the air out from in front o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 44 publications
(29 reference statements)
1
46
0
Order By: Relevance
“…11. This is an easier setup than the multi-domain finite difference setup in [19], albeit with difficulties in the implementation of reflective boundary conditions along the wedge except for special angles such as the 60°angle that we have tested. In the right hand side of Fig.…”
Section: Two-dimensional Systemsmentioning
confidence: 97%
See 1 more Smart Citation
“…11. This is an easier setup than the multi-domain finite difference setup in [19], albeit with difficulties in the implementation of reflective boundary conditions along the wedge except for special angles such as the 60°angle that we have tested. In the right hand side of Fig.…”
Section: Two-dimensional Systemsmentioning
confidence: 97%
“…To partially overcome this restriction, a multi-domain finite difference WENO scheme is proposed in [25]. Even though this multi-domain approach is performing well in many complicated applications [25,19], it does have the drawback that it is no longer strictly conservative.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the simulations are intended to show the compelling advantage in shock-mitigation and drag-reduction when suddenly depositing heat along a streamline (in this case, along the stagnation line) ahead of the bow shock generated by a supersonic/hypersonic cone 18 . The sustained benefit, demonstrated in the linedeposition geometry, results in extended periods of shock-mitigation/drag-reduction, without continual energy addition.…”
Section: Figure 3 Plots Of Relative Density  / O ) As a Functionmentioning
confidence: 99%
“…Other approaches to the wave drag reduction are to use the focused energy deposition. A wide variety of energy deposition techniques were investigated by laser pulse, plasma arcs, microwaves, electron beams, pulsed detonations or explosions, etc [16][17][18][19][20][21] . When the focused energy is deposited in the upstream region of a blunt body, the extremely hot gas is created instantaneously to push the surrounding gas outward 17 .…”
Section: American Institute Of Aeronautics and Astronauticsmentioning
confidence: 99%
“…If the gas temperature inside the core is sufficiently high to make the vehicle's speed be subsonic, then the bow shock wave is locally eliminated and the wave drag is reduced significantly. It is reported that as much as 96% drag reduction is obtained 17 . The energy addition can also be produced by localized combustion 21 and the recent research indicates the concept is more attractive 22,23 .…”
Section: American Institute Of Aeronautics and Astronauticsmentioning
confidence: 99%